Estágio curricular e sua contribuição na construção da identidade profissional dos estudantes da Educação Técnica de Nível Médio - Silva, Rilda Simone Maia da (2019)
The supervised curriculum internship constitutes one of the elements of educative and formative process in the technical training college courses, because it allows students to integrate the work, the science and culture knowledge. The study, like proposition of Management and Organization of Pedagogical Spaces of Technical and Professional Education, was aimed to analyze the supervised curriculum internship at EPTNM and their contribution in students professional identity construction. The Vasques (2007), Buriolla (1999), Pimenta e Lima (2017), Zabalza (2014), Marx (1996, 2012), Antunes (2010), Netto e Braz (2004), Saviani (2006, 2007), Frigotto (2005), Ramos (2004, 2009), Dubar (2005, 2006, 2009, 2012), Hall (1998), Kaufmann (2004), studies to justify the methodological and theoretical discussion. The investigation assumes the qualitative approach and involved the farming technical course students; the internship and integration coordinator and the supervisor-advisor teacher of the Itaituba EETEPA. The documental and field research, with the focus group half structured interview have based the data acquisition. The content analysis (BARDIN, 2011) have contributed to the data interpretation and the results discussion. The results point that the internship like institutional and educative act favors the professional immersion and contribute to the students identity constructions process in self knowledge and resignify movement that allow to recognize or to plan their professional identity. Besides that, we developed a mobile application named “Meu Estágio”, aiming to help in formative process of supervised curriculum internship and to contribute to students professional identity construction. The supervised curriculum internship contributes to the professional identity construction marked by work as an educational principle.